Madrasah Tsanawiyah Teachers' Perceptions of Blended Learning Implementation within Islamic Educational Institutions - Yanto, Subari; Arbain; Sakri Abdullah (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2024)
Although the concept of blended learning is widely recognized, many teachers, particularly those at Madrasah Tsanawiyah (MTs), remain unfamiliar with its principles and methods of implementation. In response, the Ministry of Religious Affairs of the Republic of Indonesia, through the Education and Training Agency in Makassar, organized training for MTs teachers on blended learning. This study aimed to examine the perceptions of Madrasah Tsanawiyah teachers regarding the use of blended learning in Civic and Environmental Education. Adopting a descriptive quantitative approach, the study involved a population of 120 teachers, participants in the training, which was divided into five different classes. Using purposive sampling, a sample of 29 teachers was selected, focusing on those teaching Civic Education. Data was collected through a questionnaire and analyzed descriptively, with results categorized into five groups. The findings revealed that teachers’ perceptions of blended learning were generally positive, with a mean score of 3.6, categorized as "good." The perceived quality of IT facilities in the training received an average score of 3.90, also categorized as "good." Teachers' perceptions of peer activities during the training averaged 4.3, indicating a "good" rating. Perceptions of the role of resource persons and training organizers were even more favorable, with both receiving an average score of 4.6, categorized as "very good." These results are expected to provide valuable insights for the implementation of future training programs that utilize blended learning, particularly within Islamic educational settings. Abstrak: Meskipun konsep pembelajaran blended learning telah dikenal luas, banyak guru, khususnya guru Madrasah Tsanawiyah (MTs), yang masih belum memahami prinsip dan cara penerapannya. Sebagai respons terhadap hal ini, Kementerian Agama Republik Indonesia melalui Badan Pengembangan dan Pendidikan Kementerian Agama di Makassar menyelenggarakan pelatihan bagi guru MTs mengenai blended learning. Penelitian ini bertujuan untuk mengkaji persepsi guru Madrasah Tsanawiyah terhadap penggunaan metode blended learning dalam Pendidikan Kewarganegaraan dan Lingkungan Hidup. Dengan menggunakan pendekatan deskriptif kuantitatif, populasi penelitian ini terdiri dari 120 guru peserta pelatihan yang dibagi dalam lima kelas berbeda. Menggunakan teknik purposive sampling, sampel penelitian sebanyak 29 guru dipilih, yang berfokus pada guru Pendidikan Kewarganegaraan. Data dikumpulkan melalui kuesioner dan dianalisis secara deskriptif, dengan hasil yang dikategorikan ke dalam lima kelompok. Temuan menunjukkan bahwa persepsi guru terhadap blended learning secara keseluruhan positif, dengan rata-rata skor 3,6, yang termasuk dalam kategori "baik." Persepsi terhadap kualitas fasilitas TI dalam pelatihan berbasis blended learning memperoleh rata-rata skor 3,90, yang juga termasuk dalam kategori "baik." Persepsi guru terhadap kegiatan teman sejawat selama pelatihan memperoleh rata-rata skor 4,3, yang masuk dalam kategori "baik." Persepsi terhadap peran narasumber dan penyelenggara pelatihan sangat positif, dengan keduanya memperoleh rata-rata skor 4,6, yang termasuk dalam kategori "sangat baik." Hasil penelitian ini diharapkan dapat memberikan wawasan yang berharga untuk implementasi program pelatihan di masa depan yang menggunakan metode blended learning, khususnya di lembaga pendidikan Islam.